Supply and demand in the labor market: personnel development, organizational-behavioral aspect, forecasting - Savchenko, Olga; Kunos, István; Posokhov, Igor Mikhailovich; Venesaar, Urve; Poberezhny, Roman; Nesterenko, Roman; Poberezhna, Kateryna; Lukianytsia, Alina (FOP Rogko S.G., 2016)
The book is prepared by a team of authors within the framework of the international TEMPUS Project «ICo-op». The book is dedicated to the study of the features of tools to focused demand and supply in the labor market. The authors summarized Ukrainian and foreign experience of studying processes related with the peculiarities of research leadership and entrepreneurship in the context of human capital. Particular attention is paid to the development of professional competence of future engineers and productivity already operating engineers and technical staff. The problems of development of methods and models of personal development, forecasting labor market needs based on professional competency profiles are considered. For students, researchers and teachers of universities and for enterprise managers, entrepreneurs-innovators.
Keywords: globalization; professional training; leadership; business; human capital; engineering personnel